Isolation and characterization of marine bacteria with potential petrophilic activity. - Alzuelo, Rhetta May (Iloilo City UPHSI, 2001)
So many environmental problems beset our world. One of these problems is marine pollution, specifically, oil spill which can create great damage in our environment. Oil spills, which may have long and short term effects has to be cleaned up as soon as it happens. This is to prevent it from doing further harm. Bioremediation is the process involved in the clean-up activity. This uses microorganisms in cleaning up an oil spill. This study was intended to isolate and characterize at most 3 dominant bacteria species from the shore near Fort San Pedro. This study was also aimed to determine the oil degrading capacity of the isolated species in terms of lowering the density of oil droplets in lessening the size of oil droplets. Lastly, this study was also objected to determine the feasibility of using these organisms in cleaning up oil spills. This study is significant because it may lead to the isolation and characterization of possible petrophilic bacteria. Water samples were collected and the three most dominant species of bacteria were isolated. The pure isolates were then characterized based on the shape, gram reaction, catalese reaction, and the ability to degrade various organic molecules using the rapid kit of Becken Dickinson BBL Crystal Identification Systems. The results showed that the three most dominant species of bacteria were isolated. Two of which were gram-positive and the other one is gram-negative. The three species were catalase positive and have round shapes. Using the one-way ANOVA, the results showed that the mean size of oil droplets in treatment 1 (control) was significantly higher than the other three treatments but there was no significant difference between the mean sizes of oil droplets between treatments 2, 3 and 4. This might be because the bacteria in these treatments belong to the same genera. There was no significant difference between the mean density of oil droplets in all treatments. Because of the ability of the 3 bacterial species to significantly decrease the size of oil droplets, they might be potential petrophiles that can be used for bioremediation of oil spills.
Research II : Research Manuscripts
Keywords: Marine bacteria